Quantitative analysis of social and financial market development - Barnett, William A.; Sergi, Bruno S. (Bingley, U.K. : Emerald Publishing Limited, 2022)
This 30th volume of the International Symposia in Economic Theory and Econometrics explores the latest social and financial developments across Asian markets. Chapters cover a range of topics such as the impact of COVID-19 related events in Southeast Asia along the determinants of capital structure before and during the pandemic; the influence of new distribution concepts on macro and micro economic levels; as well as the effects of long-term cross-currency basis swaps on government bonds. These peer-reviewed papers touch on a variety of timely, interdisciplinary subjects such as real earnings impact and the effects of public policy. Together, Quantitative Analysis of Social and Financial Market Development is a crucial resource of current, cutting-edge research for any scholar of international finance and economics.
Chapter 1. Effect of related party transaction and political connection on real earnings management: Study on manufacturing companies listed in indonesia stock exchange / Agustin Palupi and Lusia Tania Aurelia -- Chapter 2. Exchange rate volatility and tourist arrivals from asean to Malaysia / Eliza Nor, Tajul Ariffin Masron, and Hu Xiang -- Chapter 3. The impact of long-term cross-currency basis swap on Japanese government bonds: Analysis of different non-traditional monetary policy regimes / Takayasu Ito -- Chapter 4. The impact of covid-19-related events on indonesian composite and sectoral Index / Muhammad Hasan Ghazali and Taufik Faturohman -- Chapter 5. Customer satisfaction of e-wallet user: An adoption of information system success model / Fariq Rahadiyan Chalik and Taufik Faturohman -- Chapter 6. Stable financial performance as the antecedent of esg activity and firm value relationship: An evidence from indonesia / Yavida Nurim, Nung Harjanto, Paulina I. Prabawati, and Nur R. Wijaya -- Chapter 7. An initial study of knowledge sharing policies in higher education / Lina Anatan -- Chapter 8. An empirical analysis of firm-specific determinants of capital structure before and during covid-19 pandemic: Evidence from listed hotels, restaurants, and tourism entities on the indonesia stock exchange / Taufik Faturohman and Rashifa Qanita Noviandy -- Chapter 9. Modern concepts of distribution of knowledge and their influence on the process of diffusion of innovations on macro and micro levels of economy / Mikhailov Fedor Borisovich, Miasnikov Dmitrii Alekseevich, and Fakhrutdinov Bulat Ildarovich -- Chapter 10. Are unhappy people more likely to be religious? Evidence from Chinese rural elderly / Liying Xia, Jianbo Zhang, and Xuelin Ma.
Includes bibliographical references and index.
Print version record.
Keywords: elektronické knihy; electronic books; Finance -- Econometric models; Economic policy -- Econometric models; Business & Economics -- Econometrics; Econometrics